Pemberdayaan Mahasiswa Melalui Program Mahasiswa Penting (Peduli Stunting) melalui Edukasi Pencegahan Stunting bagi Remaja di SMA/SMK Kota Medan - Widiya Nisa; Apriliani Apriliani (FKM UIN Sumatera Utara Medan, 2025)
Stunting remains a major public health issue in Indonesia. Preventive efforts should not only focus on toddlers but must also target adolescents as future parents, equipping them with adequate knowledge from an early age. This community service program aimed to empower university students through the